1989
DOI: 10.1002/gps.930040210
|View full text |Cite
|
Sign up to set email alerts
|

Double‐blind controlled withdrawal of thioridazine treatment in elderly female inpatients with senile dementia

Abstract: SUMMARYThirty-six female inpatients with a clinical diagnosis of senile dementia, Alzheimer type, were entered into a doubleblind withdrawal of their established thioridazine. Over a four-week period there were no significant differences between the two study groups in terms of cognitive function, behaviour or physical state. There was no evidence of a withdrawal phenomenon and the use of replacement medication was at a similar low level in the two groups. Although significant differences were not established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…These findings are in accordance with other reports (Mann et al, 1986;Gilleard et al, 1983;Dehlin and FranzCn, 1985), and neuroleptic medications have become a mainstay in the treatment of the agitated elderly demented patient (Risse and Barnes, 1986). However, their usefulness has been questioned (Barnes et al, 1982;Findlay et al, 1989). Mann et al (1984 emphasize that medication tends to be higher in a nursing-medical model than in a social model of care.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in accordance with other reports (Mann et al, 1986;Gilleard et al, 1983;Dehlin and FranzCn, 1985), and neuroleptic medications have become a mainstay in the treatment of the agitated elderly demented patient (Risse and Barnes, 1986). However, their usefulness has been questioned (Barnes et al, 1982;Findlay et al, 1989). Mann et al (1984 emphasize that medication tends to be higher in a nursing-medical model than in a social model of care.…”
Section: Discussionmentioning
confidence: 99%
“…From these 47 studies, 29 were excluded because they were part of an educational program to reduce antipsychotic prescription, 7 were excluded because of the observational study design and 1 was excluded because 2 studies [18,25] were the same study with a different follow-up period and outcomes reporting. Therefore, 10 studies [18,19,21,22,23,24,26,35,36,37] were entered into the qualitative data synthesis. Among the studies in the qualitative data synthesis, 1 study [35] was excluded from the meta-analysis because the medication discontinuation combined antipsychotics and other psychotropic medications and did not report the results separately.…”
Section: Resultsmentioning
confidence: 99%
“…Among the studies in the qualitative data synthesis, 1 study [35] was excluded from the meta-analysis because the medication discontinuation combined antipsychotics and other psychotropic medications and did not report the results separately. Finally, 9 studies [18,19,21,22,23,24,26,36,37] were entered into a meta-analysis. Each of the 9 studies can only provide some, but not all, data for different outcome variables.…”
Section: Resultsmentioning
confidence: 99%
“…The timescale and extent of this can be likencd to that seen in schizophrenics and in normal volunteers. No definite evidence emerged that PRL levels might be useful as markers of disease severity or response to neuroleptic therapy.KEY woms-Thioridazine, prolactin, dementia.In a previous publication (Findlay et al, 1989) we have reported a study into the behaviour of thioridazine treatment in a population of elderly female inpatients with a diagnosis of senile dementia. Over the period of the study, there were no withdrawal phenomena, and although there was a trend which showed a decline in side-effects for the group in which thioridazine was discontinued, the difference from the group in which treatment was continued was not statistically significant.…”
mentioning
confidence: 98%
“…In a previous publication (Findlay et al, 1989) we have reported a study into the behaviour of thioridazine treatment in a population of elderly female inpatients with a diagnosis of senile dementia. Over the period of the study, there were no withdrawal phenomena, and although there was a trend which showed a decline in side-effects for the group in which thioridazine was discontinued, the difference from the group in which treatment was continued was not statistically significant.…”
mentioning
confidence: 99%